Comparison of changes in blood group, hemogram and biochemical parameters in healthcare workers with and without COVID-19 - Turan, Atakan; Öğüt, Hamdi; Bozkurt, Hayri; Ayyıldız Varol, Aylin (The European Research Journal, 2025)
Objective: This study aimed to evaluate blood groups and some hematologic and biochemical parameters in healthcare workers with and without COVID-19. Methods: The sample consisted of 1232 healthcare workers who consented to participate in the study after being informed about its purpose and methodology. The study's case group consisted of 704 individuals who got COVID-19, whereas the control group consisted of 528 individuals who didn't get the virus. A survey conducted online was used to gather data. The study was conducted with adherence to ethical norms. Results: Participants in the case and control groups showed a significant difference in their vitamin D level variables, and those with low vitamin D levels were 1.9 times more likely to contract COVID-19 than those with normal levels. Blood glucose, lactate dehydrogenase (LDH), ferritin, troponin-I, D-dimer, C-reactive protein (CRP), anti- human immunodeficiency virüs (HIV), white blood cell, hemoglobulin, platelets, lymphocyte, and neutrophil averages were significantly different between the case and control groups when the biochemistry values of the participants were compared (P